IJCM_294A: COVID-19 vaccination status and willingness for booster dose among staff and students of tertiary care institute - Sharma Nikita; Thakare Meenal Madhukar (Wolters Kluwer Medknow Publications, 2024)
Background: Exposure to new COVID-19 variants and decline in herd immunity may result in new or repeat infection. The booster dose may face certain challenges that result in low uptake. The aim of the study was to assess the COVID-19 vaccination status and willingness of medical staff and students to receive further booster doses. Objectives: 1. To assess the willingness of staff and students regarding booster dose of any COVID-19 vaccine. 2. Explore reason behind the willingness of booster dose and nasal route. Methodology: A cross sectional study was conducted among the staff and students of a tertiary care institute. With 5% margin of error, 95% confidence interval, intention to receive booster vaccine as 55.3% and 10% non-response rate, the sample size was calculated as 312. The participants received a web based semi-structured questionnaire through email and WhatsApp. The data was analyzed using SPSS version 24. Descriptive analysis was performed in the form of frequency and proportions for categorical variables. Results: About 302 participants responded to the survey. About 51.3% of them were females and 61.2% belonged to 18-29 year age group. The health workers, ancillary staff and students were 37.7%, 40% and 22.2% respectively. About 49.3% received a precaution dose while 49% had received 2 doses of any COVID-19 vaccine. About 72.1% of the participants were willing to receive another booster dose. Perception of vaccine as an immunity booster was the top reason for the willingness. About 34.2% (25/73) of them preferred nasal route for the booster with 66.3% (21/33) perceiving it convenient to administer. Conclusion: Knowledge about the acceptance of COVID-19 vaccine and perceptions regarding the booster dose may help to increase the readiness of medical community to uptake the booster. Alternative routes of administration and reasons for willingness may reduce the skepticism for booster dose.